2015
DOI: 10.1016/j.ypmed.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behaviour and dietary patterns: A systematic review and meta-analysis

Abstract: Objective Promoting adherence to healthy dietary patterns is a critical public health issue. Models of behaviour, such as the Theory of Planned Behaviour (TPB) allow programme designers to identify antecedents of dietary patterns and design effective interventions. The primary aim of this study was to examine the association between TPB variables and dietary patterns. Methods A systematic literature search was conducted to identify relevant studies. Random-effects meta-analysis was used to calculate average co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
143
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 44 publications
16
143
4
4
Order By: Relevance
“…We demonstrated the importance of a simultaneous test by conducting a new analysis of two recent meta-analyses of the theory of planned behavior applied to two health behavioral contexts: alcohol (Cooke et al, 2014) and dietary behaviors (McDermott et al, 2015). Specifically, we conducted a path analysis specifying theory predictions using the meta-analytically derived correlations behavioral control on intentions (β < .075) in alcohol behaviors is a cause for concern for theory validity (c.f., Seaton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated the importance of a simultaneous test by conducting a new analysis of two recent meta-analyses of the theory of planned behavior applied to two health behavioral contexts: alcohol (Cooke et al, 2014) and dietary behaviors (McDermott et al, 2015). Specifically, we conducted a path analysis specifying theory predictions using the meta-analytically derived correlations behavioral control on intentions (β < .075) in alcohol behaviors is a cause for concern for theory validity (c.f., Seaton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, meta-analytic syntheses of relations among constructs from a given theory that use path analysis to test the pattern of effects among its constructs are still relatively rare. For example, two recent meta-analyses of the theory of planned behavior in two health-related behaviors alcohol (Cooke et al, 2014) and dietary (McDermott et al, 2015) behaviors, respectively, reported zero-order meta-analytically derived correlations among the variables but did not conduct a path analysis to test model predictions. In both articles the initial stages of the analyses were competently conducted and included an informative search and analysis of candidate moderators to resolve heterogeneity in the effects.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This is not an unusual feature in studies as not all domain changes are associated with GI over time [38,39]. This perhaps can be attributed to the context-specific settings of the study, the type of intention, and indeed the general intention practice [40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…A review of 22 studies showed a moderate to severe association between the constructs of the behavioral intention and adherence to dietary patterns (22). A study demonstrated that the attitude, subjective norm, and perceived behavioral control were the significant predictors of the intention of women with HIV toward the use of dietary supplements (23).…”
Section: Introductionmentioning
confidence: 99%